Homologous recombination and the yKu70/80 complex exert opposite roles in resistance against the killer toxin from Pichia acaciae - Klassen, Roland; Krampe, Stefan; Meinhardt, Friedhelm (DNA repair, 2007)
The linear plasmid (pPac1-2) encoded killer toxin (PaT) of the yeast Pichia acaciae arrests sensitive Saccharomyces cerevisiae cells in the S-phase of the cell cycle and induces mutations. Here we provide evidence for opposite effects in PaT resistance of homologous recombination (HR) and non-homologous end joining (NHEJ), the two alternative repair mechanisms acting on DNA double strand breaks (DSB). As mutants defective in genes of the RAD52 epistasis group react hypersensitive and cells lacking YKU70 or YKU80 are partially resistant, the yKu70/80 complex facilitates PaT toxicity, whereas HR is antagonistic. In contrast to yku70 and yku80, lif1 mutants, the latter being defective in the ligation step of NHEJ, are PaT sensitive, confining toxicity promoting effects of NHEJ to the DSB end binding Ku proteins. Since rad52 yku80 double mutants display strong hypersensitivity, yku80 mediated resistance depends on HR. Opposite effects of the yKu70/80 complex and HR are consistent with the occurrence of replication dependent (one sided) DSBs in PaT treated cells. Concordantly, two cellular markers signaling DSBs are induced during PaT mediated S-phase arrest, i.e. histone H2A phosphorylation and formation of subnuclear repair foci by GFP tagged recombination protein Rad52. As only moderate chromosome fragmentation could be detected by PFGE, transient occurrence and efficient in vivo repair of PaT induced DSBs is assumed. Consistent with replication dependent DSB formation induced by PaT, we demonstrate a protective function of the RecQ helicase Sgs1 and the structure specific endonuclease Mus81, both of which are considered to be involved in processing and restart of stalled replication forks.